MASALAH KENAKALAN REMAJA JUVENILE DELINQUENCY PROBLEM - Nuraeni, Hilma (LPPM Universitas Ibn Khaldun, Bogor, 2022)
Abstract This article aims to see how the problem of juvenile delinquency that occurs in today's society is a problem that can be solved with teamwork. Team work here consists of the role of parents, the role of the teacher, and also the youth environment. From several journals cited, the authors conclude that juvenile delinquency is currently being influenced by the increasingly high current of globalization among the public, especially young people. If this high challenge of globalization is not fortified with factors, be it biological, psychological, and even peers, this will result in adolescent moral decadence. The moral decadence of youth that is currently being echoed is about juvenile delinquency, from mild to severe. Abstrak Penelitian ini bertujuan untuk melihat bagaimana masalah kenakalan remaja yang terjadi di masyarakat kini merupakan masalah yang bisa diselesaikan dengan adanya kerja tim. Kerja tim disini ialah terdiri dari peran orang tua, peran guru, dan juga lingkungan remaja. Dari beberapa jurnal yang dikutip, penulis menyimpulkan bahwasannya kenakalan remaja saat ini dipengaruhi oleh arus globalisasi yang semakin tinggi dikalangan masyarakat terutama anak muda. Tantangan globalisasi yang tinggi ini apabila tidak dibentengi dengan faktor baik itu biologi, psikis, bahkan teman sebaya, maka hal ini akan mengakibatkan sebuah dekadensi moral remaja. Dekadensi moral remaja yang saat ini tengah digaungkan ialah perihal kenakalan remaja, dari yang sifatnya ringan hingga berat.